Identification of The Effect of Hyberbaric Oxygen Therapy (HBOT) on Blood Pressure Lowering Effects in Hypertension Patients - Karindra Amadea Susetiyo; Agus Subagjo; Primadita Syahbani; Iqlima Rahmawati; Ikhsanuddin Qothi (Cardiovascular and Cardiometabolic Journal, 2022)
Hypertension is a leading cause of death worldwide including in Indonesia. The World Health Organization (WHO) estimates that currently the global prevalence of hypertension is 22% (WHO, 2019). In 2018 the prevalence of hypertension in Indonesia reached 34,11% (Riskesdas, 2018). Every year, it is estimated that 10.4 million deaths are caused by hypertension (Unger et al., 2020). Hyperbaric Oxygen Therapy (HBOT) is a therapy with pure oxygen concentration (100%) in a high pressure room (Ortega et al., 2021). In previous studies it was found that HBOT improves the effects of vasodilation (Mihaljevic et al., 2018). However, other studies mention different results. It was found that HBOT initiates vasoconstriction and increases systemic vascular resistance. This causes a decrease in nitrite oxide (NO) production and increase NO oxidation (Goyal et al., 2021). Apart from a variety of different study results, the use of HBOT has indeed been widely studied even though it has not found a clear meeting point on the effects of blood pressure reduction on hypertension patients. Therefore, the author aims to find out more clearly the mechanism and benefits of hyperbaric oxygen therapy against decreased blood pressure in hypertension patients.           Keywords: Hyperbaric Oxygen Therapy, Hypertension